Health index and risk assessment models for Gas Insulated Switchgear (GIS) operating under tropical conditions. (May 2020) - Purnomoadi, A.P.; Mor, A. Rodrigo; Smit, J.J.
Highlights: The failure rate of Gas Insulated Switchgear (GIS) operating under tropical conditions is about twice the value reported by the third CIGRE's survey in 2007. Three major failure modes that lead to catastrophic failure of a GIS in tropics are the insulation breakdown, the primary joint-conductor failure, and the driving mechanism failure. The Health Index states the GIS health status which covers the dominant and the non-dominant subsystems condition-parameters. Besides, the surge arrester is scored separately to emphasize its importance since lightning is frequent in tropics. There are seven approaches possible for the generation of norms in the Health Index. They include the statistical analysis and through the laboratory tests. The risk assessment model combines the six-parameters that increasing the probability of failure of a GIS operating under tropical conditions and the consequences measured by the company's business' values. Abstract: This article contains the development of the Health Index (HI) and the Risk Assessment (RA) models for Gas Insulated Switchgear (GIS) operating under tropical conditions. A case study of 631 bays of GIS in tropics with service time from 1 up to 30 years is used during the development of the models. The basis for the HI model is the condition assessment of subsystems in GIS. This assessment translates the measured parameters from GIS subsystems into condition status based on a set of norms and rules. The condition status is presented in a score, where the non-linear scaling is chosen as it allows the poor parameters to really stand out. On the other hand, the RA model calculates the risk of a GIS major failure. The Total Failure Probability (TPF) unifies six risk indicators of GIS failures under tropical conditions. The risk may fall into one of the four categories, namely: Low, Medium, High, and Very High.